The subprime crisis and stock index futures markets integration - Bakri, Abdul Karim; Jais, Mohamad (The Journal of Risk Finance, 2011)
Purpose – The purpose of this paper is to examine the effects of the current global crisis on the integration and co-movements of selected stock index futures markets. Design/methodology/approach – Time series techniques of cointegration and weekly data covering the period from January 2001 to December 2009 were used in this study. The period of analysis was divided into two periods, namely the pre-crisis period (January 2001-July 2007) and during crisis period (August 2007-December 2009). Findings – No evidence was found of cointegration among the stock index futures markets in both periods. Accordingly, the 2007 subprime crisis does not seem to affect the long-run co-movements among the stock index futures markets. Practical implications – The stock index futures markets provide opportunity for the potential benefits from international portfolio diversification and hedging strategies even after the subprime crisis. The stock index futures significantly extended the variety of investment and risk management strategies available to investors. Originality/value – Examining the effects of the US subprime crisis on the stock index futures markets integration, to the best of the authors’ knowledge, goes clearly beyond the existing literature on the subject matter.